Prospects and Design Insights of Neat Ionic Liquids as Supercapacitor Electrolytes - Lethesh, Kallidanthiyil Chellappan; Bamgbopa, Musbaudeen O.; Susantyoko, Rahmat Agung (Frontiers in Energy Research, 2021)
Ionic liquids present an opportunity to design efficient electrolytes for supercapacitors, which are among the most extensively studied electrochemical energy storage systems. Ionic liquids are promising candidates for supercapacitor electrolytes because they can eliminate issues associated with aqueous and organic solvent-based electrolytes, such as narrow operating potential windows, safety, and performance. The full potential of ionic liquids as electrolytes in supercapacitors need to be further explored due to promising previous efforts invested in ionic liquid-based electrolyte systems for supercapacitor. This review aims to provide an outlook on neat (pure) ionic liquids applied as supercapacitor electrolytes to isolate the prospects and influences of ionic liquids in supercapacitor electrolyte systems. This work primarily focuses on ionic liquid chemistry links to their performance in supercapacitor electrolytes. Deduced features of importance to supercapacitor performance include the presence of functional groups in the ionic liquids, the ionic liquids physicochemical and electrochemical properties. With the different classes of ionic liquids evaluated, ion size-pore size matching of ionic liquid electrolytes and electrode materials, respectively, affect resulting capacitances and energy densities. Several design strategies to enhance supercapacitor performance by improving ionic liquid transport and electrochemical properties are proposed. The proposed strategies and obtained insights consequently informed further discussions on challenges associated with the commercialization of ionic liquids electrolytes.